Wideband and flat-gain amplifier using high concentration Erbium doped fibers in series double-pass configuration - Hamida, Belal Ahmed; Latiff, A.A.; Cheng, X. S.; Ismail, M.A.; Naji, Ahmed Wathik; Khan, Sheroz; Al-Khateeb, Wajdi Fawzi Mohammed; Ahmad, H.; Harun, S.W. (2012)
A wide-band and flat gain Erbium-doped fiber amplifier (EDFA) is demonstrated using a gain media of high concentration Silica-based erbium doped fiber (EDF). The amplifier has two stages comprising a 1.5 m and 9 m long EDF optimized for C-band and L-band operations respectively, in a double-pass series configuration. The CFBG is used in both stages to allow a double propagation of signal and thus increases the attainable gain in both C- and L-band spectra. At an input signal power of -30 dBm, a flat gain of 22 dB is achieved with a gain variation of ±3 dB within a wide wavelength range from 1530 to 1600nm. The corresponding noise figure varies from 4 to 8 dB within this wavelength region.